The Effect of Thallus Weight on Growth Seaweeds Sargassum duplicatum in Controlled Container - Irfan, Muhammad; Subur, Riyadi (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2021)
The potential of seaweed S. duplicatum is quite abundant in this area, but efforts to develop its cultivation have not been developed until now. The reason is that there is no information related to the existence of this type of seaweed in North Maluku, especially in the city of Ternate. To recognize and utilize the existing potential, it is necessary to develop its cultivation. The objectives of this research are: to determine the effect of different thallus weights on the growth of S. duplicatum seaweed and determine the weight of the thallus which has the best effect on the growth of seaweed S.. dupicatum . The collection of seaweed S. duplicatum seedlings was carried out naturally in Sasa waters, at a depth of about 1 meter. The seeds obtained are then put into a container (plastic bag). After that, it is taken and then taken to the laboratory to be weighed. The weight of the thallus that has been weighed is then tied to each spanning rope which is placed into each container according to its thallus weight, namely thallus weights of 50, 70 and 90 grams. The container used for maintenance was fiber tub with a container length of 90 cm, width of 30 cm, 9 (nine) units. The results showed that the thallus weight of 90 grams gave the best results for the absolute weight growth of 101.66 grams and the thallus 50 grams gave the best results for the relative growth rate of 1.437%.